Grace under fire [compact disc, unabridged] - Garwood, Julie (Garwood, Julie. Buchanan-Renard series., 2022)
"Grace Isabel MacKenna had a hundred things to do today. Killing someone wasn't one of them. She checks into the hotel and then decides to go for a brisk walk. But after getting lost, she ends up with a wounded man stumbling into her arms, and then his shooter coming after them both. When she fires back in self-defense, she doesn't expect him to drop dead. Thanks to the Buchanans dispatching Navy SEAL and now a lawyer Michael Buchanan to help her deal with the police, Isabel endures hours of interrogation and is finally free to go. Isabel knows she should be grateful for Michael's help, but since she's harbored an extreme dislike for him for years, gratitude is difficult to muster. Michael has appointed himself her de facto guardian, and she's stuck with him despite their constant bickering and sizzling attraction. Mysterious threats against Isabel surface, and before they can deal with their growing feelings for each other, Michael and Isabel must first survive."--Container.